Late-glacial Coleoptera and the paleoclimate at Hirtles, Nova Scotia - Miller, Randall (Atlantic Geology, 1995)
Paleoentomological studies of Coleoptera from a late-glacial site at Hirtles, Nova Scotia, Canada, produced a tundra-treeline to northern boreal assemblage during the interval 12,300 to 11,700 years B.P. This is one of the oldest late-glacial buried organic deposits in the Maritime Provinces of Canada and provides fossil beetle evidence for recently deglaciated environments in the region. Bark beetles indicate the presence of trees, perhaps as early as 11,900 years B.P. A comparison can be made with contemporaneous sites in central and eastern North America where coleopteran evidence suggests warmer temperatures. Coleoptera fossils demonstrate evidence of a climatic gradient from the Great Lakes to eastern Canada during this time interval possibly greater than occurs today.